Irritable bowel syndrome in medical students from Lima, Peru, during the COVID-19 pandemic, using virtual questionnaires according to the Rome IV criteria: prevalence and associated factors - Medina-Pérez, Roberto (2024)
Irritable bowel syndrome (IBS) is a functional gastrointestinal (GI) disorder, characterized bychanges of the intestinal habit associated with abdominal pain. This study analyzed factorsassociated with this pathology during the COVID-19 pandemic, and it was seen that the impact of IBS was higher in young women who had ongoing studies in the medical field. Objectives: Determine the prevalence of IBS in medical students and explore the associated factors with the increase of its symptoms, through the use of digital tools. Materials and methods: Descriptive observational study with exploration of associations, with nonprobabilistic sampling, until reaching the minimum sample of 110 participants with a confidence interval of 95%, finally having a total sample of 131 students, distributed in 3 proportional and representative subgroups of the last 3 years of study of the medical career from a university from Lima, Peru. The inclusion criteria were students of both sexes and legal age, who gave their consent to participate and did not have risk factors for GI disease. Once the study was approved, the link of a validated virtual questionnaire was shared through the institutional email. To explore the associated factors, the Chi-square test was used with a statistical significance of p < 0.05. Results: Responses were obtainedfrom 195 students; 64 (32.82%) of them had at least one exclusion criteria, finally having a sample size of 131; 64 (48.85%) were women, and 52 (39.69%) were from 7th year. Using the Rome IV criteria, 23 participants were classified as having IBS, which indicates a prevalence of 17.56%, 14 (60.87%) of them were women and 10 (43.48%) were from the 7th year (last year of study of the medical career in Peru). It was observed that 1 in 3 students (32.06%) had chronic abdominal pain, and 1 in 2 (53.44%) reported having a history of Major Depression or Generalized Anxiety Disorder. Of the total, 51 (38.93%) had a history of having a positive COVID-19 test result. Regarding the associated factors, a significant association was only found between IBS and the diarrhea type, classified according to the Bristol Scale. Conclusions: The prevalence of IBS in medical students was 17.56%, the highest compared with studies in the general population and in medical students using Rome IV criteria. Of the associated factors, the clinical presentation of diarrhea, according to the Bristol scale, was associated with IBS.